Chemo‐ and Regioselective Multiple C(sp2)−H Insertions of Malonate Metal Carbenes for Late‐Stage Functionalizations of Azahelicenes. (1st September 2022) - Nikolova, Yana; Fabri, Bibiana; Moneva Lorente, Pau; Guarnieri‐Ibáñez, Alejandro; de Aguirre, Adiran; Soda, Yoshiki; Pescitelli, Gennaro; Zinna, Francesco; Besnard, Céline; Guénée, Laure; Moreau, Dimitri; Di Bari, Lorenzo; et al.
Abstract: Chiral quinacridines react up to four times, step‐by‐step, with α‐diazomalonates under Ru II and Rh II catalysis. By selecting the catalyst, [CpRu(CH3 CN)3 ][PF6 ] (Cp=cyclopentadienyl) or Rh2 (oct)4, chemo and regioselective insertions of derived metal carbenes are achieved in favor of mono‐ or bis‐functionalized malonate derivatives, respectively, (r.r.>49 : 1, up to 77 % yield, 12 examples). This multi‐introduction of malonate groups is particularly useful to tune optical and chemical properties such as absorption, emission or Brønsted acidity but also cellular bioimaging. Density‐functional theory further elucidates the origin of the carbene insertion selectivity and also showcases the importance of conformations in the optical response. Abstract : Chiral quinacridines react chemo‐ and regioselectively with α‐diazomalonates under Ru II /Rh II catalysis, up to four times, achieving a stepwise late‐stage multi‐functionalization of the [4]helicene scaffold. Absorption, emission or Brønsted acidity but also cellular bioimaging are readily tuned. Density‐functional theory elucidates the carbene insertion selectivity and clarifies the importance of conformations in the optical response.